2014
DOI: 10.1039/c4cc01204f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of nanoantennas on the bacterial outer membrane

Abstract: We demonstrate a simple manipulation of gold nanoparticles that creates a structure-dependent nanometer-scale antenna on the surface of bacteria. Our studies illuminate the concept of the "effective use of light" based on the absorption and emission of light by antennas formed on bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…In contrast, almost all of the negatively charged Au NPs were observed on the substrate instead of the bacterial surface, indicating that the electrostatic force dominated the interaction between the Au NPs and the bacterium. 18 A dark-field microscopic observation was carried out to evaluate the light-scattering characteristics of the Au NPs adsorbed on a bacterium, as shown in Fig. 4B.…”
Section: Light-scattering Characteristics Of Metal Nps On a Single Bamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, almost all of the negatively charged Au NPs were observed on the substrate instead of the bacterial surface, indicating that the electrostatic force dominated the interaction between the Au NPs and the bacterium. 18 A dark-field microscopic observation was carried out to evaluate the light-scattering characteristics of the Au NPs adsorbed on a bacterium, as shown in Fig. 4B.…”
Section: Light-scattering Characteristics Of Metal Nps On a Single Bamentioning
confidence: 99%
“…16 Gram-negative bacteria possess a negatively charged surface (-40 --20 mV) when dispersed in a wide range of pH. 17,18 This suggests that the negative charge is pre-dominant on the surface of a bacterium due to phosphate and carboxylate groups compared with amino groups which are included in LPS. 19 To achieve accurate cell imaging, it is necessary to design the NPs in terms of the sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium formate (0.10 M) and tetrachloroauric(III) acid (2.0 mM) were added to the bacterial suspension (20 mL), which was then incubated under a nitrogen-saturated atmosphere at 25 C for 24 h. The color of the suspension changed from light yellow (tetrachloroauric acid color) to light red purple over a period of 3 h, and gradually became dark reddish-purple because of a localized surface plasmon resonance (LPSR) of the Au NPs. 17,18 In accordance with the color change, the UV-vis spectra revealed no peaks at the early stage of incubation; however, a peak at approximately 550 nm gradually became intense, as shown in Fig. 1A.…”
mentioning
confidence: 64%
“…Thus, DFM imaging with a good contrast enables us to visualize metal nanoparticles, [18][19][20][21][22] such as Au or Ag, and to measure the bacterial motion and high-speed rotation of bacteria flagella. [23][24][25][26][27] Since DFM images obtained in this study also showed good contrast, we tried to analyze timedepended changes of the aggregate sizes of LAB mediated by CMC.…”
Section: Resultsmentioning
confidence: 99%